Science and society in India, 1750-2000 - Bandopadhyay, Arun. (New Delhi : Manohar Publishers & Distributors, 2010)
Papers presented at a national seminar on Science and society in modern India, held at Kolkata in 2005.
Includes bibliographical references.
Keywords: Science -- India -- History -- Congresses; Science -- Social aspects -- India -- Congresses